The effect of a formulation based on maduramycin and nicarbazine on rats and broiler chickens in a subacute experiment - Dotsenko, Roman; Romanko, Maryna; Vashchyk, Yevheniia; Zakhariev, Andriy; Zemlianskyi, Andrii; Dotsenko, Ekaterina; Seliukova, Nataliia (ScienceRise: Biological Science, 2021)
The aim: to determine the effect of a preparative form of an antiemeric agent based on maduramycin and nicarbazine on the body of white rats and broiler chickens under the conditions of a subacute experiment. Materials and methods. The formulation based on maduramycin and nicarbazine was administered to rats and broiler chickens with feed for 28 days. One control and three experimental groups were formed for the experiment: Group I – animals received a complete diet without admixture of the formulation (control group), Group II – animals that were administered the formulation (by the amount of active substances) at a dose of 5.0 mg / kg, III – 25.0 mg / kg and IV – 50.0 mg / kg of feed, respectively. In order to establish the toxic effect of the formulation on the body of experimental birds on 7, 14, 28 days of the experiment and 7 days after discontinuation of the formulation, 5 heads from each group were killed under light ether anesthesia, blood samples were taken for hematological and biochemical studies. Results. During the study of the general clinical condition of rats and broiler chickens of the experimental groups, no significant changes in behavior and appearance were detected, compared with the control. Hematological parameters of broiler chickens it was found that the receipt of the formulation with feed at doses of 5, 25 and 50 mg/kg body weight, causes a decrease in hemoglobin and an increase in hematocrit in broiler chickens on day 7 of the experiment. It was found that the changes are reversible, on the 28th day of the experiment the value of these indicators was within the physiological norm. In the study of hematological and biochemical parameters of rats, it was found that the receipt of the formulation with food in doses of 25.0 and 50.0 mg/kg for 28 days, causes a decrease in hemoglobin and increase hematocrit, total protein, albumin, creatinine and urea in male rats on the 7th day of the experiment. Conclusions. Under conditions of repeated oral administration of the preparation mixture to rats and poultry at doses of 5, 25 and 50 mg/kg body weight in the absence of clinical signs of poisoning, insignificant fluctuations in hematological and biochemical parameters were identified